Effect of informed consent on patients undergoing gastrointestinal surgery and living donor liver transplantation and on their relatives in a developing country. Issue 1 (7th February 2018) - Ray, S; Mehta, N N; Mehrotra, S; Lalwani, S; Mangla, V; Yadav, A; Nundy, S
Abstract: Background: Informed consent is a systematic process for obtaining permission before conducting a healthcare intervention. In a developing country, gaining informed consent is generally perceived to be a ritual only to comply with legal requirements. The present study examined this by assessing the process of informed consent in patients undergoing gastrointestinal surgery or living donor liver transplantation (LDLT) and their relatives, based on their comprehension and overall satisfaction, in India. Methods: All patients undergoing any gastrointestinal surgery or LDLT procedure between August 2015 and July 2016 and their relatives were included, and were administered a structured questionnaire 5 days after the procedure. Results: The majority of patients (94·2 per cent) could recall the nature of their disease, the surgery performed (81·6 per cent) and anticipated complications (55·6 per cent). Among their relatives, these proportions were 97·8, 87·3 and 58·5 per cent respectively. Recall was associated with age, occupation and education among both patients and relatives. Patients undergoing LDLT, their donors and their relatives had better recall than those who had other gastrointestinal procedures ( P < 0·001). Many patients found the process of informed consent useful and reassuring. Conclusion: The details and risks of an operation were understood by most of the patients, especially those undergoing liver transplantation. Patients from developing countries can generally understand 'informed consent', and value it. Graphical Abstract: The relevance and impact of informed consent has been studied in Indian gastrointestinal (GI) surgical and liver donor liver transplantation (LDLT) patients objectively in terms of their recall of and overall satisfaction with the process and compared in a sub group analysis of the data. HPB, hepatopancreatobiliary Common incidence warrants studies exploring the role of prevention